Produtividade bacterioplanctônica e fitoplanctônica nos ecossistemas aquáticos do trecho médio da bacia do Rio Doce MG - Petrucio, Maurício Mello (2003)
This research had as major objective to quantify the existent relationships between bacterioplankton and phytoplankton production rates, determining the importance of these communities on the carbon fixation and organic matter transfer in rivers and lakes of the middle stretch of the Rio Doce basin in Minas Gerais state (southeast Brazil) during dry and rainy periods of the years 1999-2001. The concentrations of carbon, nitrogen and phosphorus and the N/P ratios were used to evaluate possible relationships between productivity and trophic status based in diel, seasonal, and annual patterns. This thesis was divided into 5 chapters approaching mainly phytoplankton and bacterial production rates in rivers and lakes of Rio Doce basin. The testing hypothesis is that production rates varies seasonally (dry and rainy periods) thus resulting in changes of the BP/PP ratios, as a consequence of changes in the inputs of allochthonous matter (nutrients) being also affected by distinct internal loads during these periods. The study was conducted in 8 rivers of the middle stretch of Rio Doce basin and in 7 lakes of the Rio Doce State Park and surrounding area, during dry and rainy periods from 1999 to 2001. The ecosystems presented a wide trophic status (from oligo to eutrophic), as well as bacterioplantonic (0.005 5.7 mg C.m-3.h-1) and phytoplanctonic (0.01 747.5 mg C.m-3.h-1) production rates. For the lotic environments, seasonality and nutrient concentration were considered the most important factors for productivity. Significant positive correlations were obtained between phosphorus concentrations and bacterial production rates. For the lentic environments seasonality was only evident for bacterial production rates with high N/P ratios, suggesting phosphorus limitation in most of the lakes. Bacterial production in spite of presenting lower values than the ones recorded for phytoplankton could be an important carbon source mainly within deep layers and more eutrophic ecosystems.